2020
DOI: 10.1016/j.ajpath.2020.06.011
|View full text |Cite
|
Sign up to set email alerts
|

The Common miRNA Signatures Associated with Mitochondrial Dysfunction in Different Muscular Dystrophies

Abstract: Secondary mitochondrial damage in skeletal muscles is a common feature of different neuromuscular disorders, which fall outside the mitochondrial cytopathies. The common cause of mitochondrial dysfunction and structural changes in skeletal muscle tissue remains to be discovered. Although they are associated with different clinical, genetic, and pathologic backgrounds, the pathomechanisms underlying neuromuscular disorders might be attributed to the complex interaction and cross talk between mitochondria and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 41 publications
1
6
0
Order By: Relevance
“…Through its suppression of KAT7 expression by binding to the 3’ UTR, miR-134-5p inhibited the KAT7-induced H3K14Ac of MnSOD and catalase, thereby decreasing the expressions of MnSOD and catalase and promoting ROS accumulation. In parallel with our study, Aksu-Menges et al [ 36 ] identified miR-134-5p as a commonly increased miRNA related to mitochondrial damage in patients with muscular dystrophy, thereby revealing a potential link between miR-134-5p and mitochondrial dysfunction.…”
Section: Discussionsupporting
confidence: 89%
“…Through its suppression of KAT7 expression by binding to the 3’ UTR, miR-134-5p inhibited the KAT7-induced H3K14Ac of MnSOD and catalase, thereby decreasing the expressions of MnSOD and catalase and promoting ROS accumulation. In parallel with our study, Aksu-Menges et al [ 36 ] identified miR-134-5p as a commonly increased miRNA related to mitochondrial damage in patients with muscular dystrophy, thereby revealing a potential link between miR-134-5p and mitochondrial dysfunction.…”
Section: Discussionsupporting
confidence: 89%
“…In an in vitro model of murine myotubes, miRNA-328-5p silencing resulted in an induction of several genes involved in mitochondrial dynamics (MFN-1, MFN-2 and OPA-1) and biogenesis (SIRT1 and PGC-1α) and in the activation of the mitochondrial unfolded protein response [40]. Furthermore, miR-382-5p was associated with mitochondrial pathways related to different neuromuscular disorders [41]. Another interesting miRNA, down-regulated in LGMDR4, is miR-376c-3p.…”
Section: Discussionmentioning
confidence: 99%
“…Alterations in miR-497 have been mainly reported in different types of cancer 33 . However, altered levels of miR-497 have also been reported in metabolic syndrome 34 , in axial spondyloarthropathy HLA-B27 + patients 35 , in Parkinson's disease 36 , in mitochondrial muscular dystrophies 37 , in pulmonary fibrogenesis 38 , and in acute cerebral infarction 39 . In bone, overexpression was found to promote differentiation and mineralization of osteoblasts through the JNK signaling pathway 40 , and more specifically through the TGF-beta1/Smads signaling pathway 41 .…”
Section: Discussionmentioning
confidence: 99%